Twelve tips to support healthcare teams to incorporate interprofessional education and collaborative practice into day-to-day workplace practices - Ford, Martelle; Martin, Priya; Sy, Michael (The Journal of Practice Teaching and Learning, 2023)
Despite a growing body of research into interprofessional education and collaborative practice (IPECP), practical strategies and initiatives are required to assist healthcare workers with implementation. Practical strategies and tips outlined in this paper can support healthcare teams to incorporate IPECP into day-to-day workplace practices. Beyond IPECP engagement, the proposed tips will assist with refining current workplace practices and processes to make them more collaborative, intentional, and streamlined at the point of care. Bearing in mind that there is no ‘one size fits all’ approach to IPECP, these tips have been developed to suit a variety of contexts and are able to be adapted and contextualised by healthcare workers and teams. These 12 tips would not only assist with the implementation of new ideas related to IPECP, but also influence sustainability considerations of these initiatives within healthcare settings.